2015
DOI: 10.1038/jhg.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese case of cerebellar ataxia, spastic paraparesis and deep sensory impairment associated with a novel homozygous TTC19 mutation

Abstract: Mitochondrial complex III (CIII) deficiency comprises a group of complex and heterogeneous genetic disorders. TTC19 mutations constitute a rare cause of CIII deficiency and are associated with neurological disorders in childhood and adulthood. Herein, we describe a 27-year-old Japanese man with cerebellar ataxia, spastic paraparesis, loss of deep sensation, mild frontal lobe dysfunction and transient psychiatric symptoms. Brain magnetic resonance imaging showed cerebellar atrophy and bilateral high-intensity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Loss-of-function mutations in TTC19 have been found in patients with cIII 2 deficiency associated with heterogeneous neurological syndromes (Ardissone et al, 2015;Atwal, 2014;Ghezzi et al, 2011;Kunii et al, 2015;Melchionda et al, 2014;Mordaunt et al, 2015;Morino et al, 2014;Nogueira et al, 2013). TTC19 ablation in D. melanogaster causes cIII 2 deficiency associated with a neurological phenotype in adult flies (Ghezzi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss-of-function mutations in TTC19 have been found in patients with cIII 2 deficiency associated with heterogeneous neurological syndromes (Ardissone et al, 2015;Atwal, 2014;Ghezzi et al, 2011;Kunii et al, 2015;Melchionda et al, 2014;Mordaunt et al, 2015;Morino et al, 2014;Nogueira et al, 2013). TTC19 ablation in D. melanogaster causes cIII 2 deficiency associated with a neurological phenotype in adult flies (Ghezzi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic mutations have been found in some of cIII 2 -related ancillary factors, including BCS1L (de Lonlay et al, 2001;Fellman, 2002;Fernandez-Vizarra et al, 2007;Hinson et al, 2007;Morá n et al, 2010;Ramos-Arroyo et al, 2009), TTC19 (Ardissone et al, 2015;Atwal, 2014;Ghezzi et al, 2011;Kunii et al, 2015;Melchionda et al, 2014;Mordaunt et al, 2015;Morino et al, 2014;Nogueira et al, 2013), LYRM7 (Dallabona et al, 2016;Invernizzi et al, 2013), UQCC2 (Tucker et al, 2013), and UQCC3 (Wanschers et al, 2014). In particular, mutations in TTC19 have been identified in patients with heterogeneous, but invariably severe, phenotypes, including early-onset, slowly progressive encephalomyopathy; adult-onset, rapidly progressive multisystem neurological failure; adult-onset spinocerebellar ataxia; and childhood or juvenile spinocerebellar ataxia with psychosis (OMIM: 613814).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first cases were reported, other TTC19 mutations have been published always associated with isolated CIII but with different clinical presentations. A progressive neurodegenerative disorder showing severe psychiatric signs and cerebellar disease was found in four Portuguese siblings born to consanguineous parents ( Nogueira et al, 2013 ), Leigh syndrome was reported in a Hispanic child ( Atwal, 2013 ) and cerebellar ataxia in Japanese adult individuals ( Morino et al, 2014 ; Kunii et al, 2015 ). All the described cases ( Table 2 ) carried non-sense or frameshift mutations leading to a truncated protein and, at least in the first reported patient samples, to undetectable TTC19 levels ( Ghezzi et al, 2011 ).…”
Section: Accessory Proteins: Assembly Factorsmentioning
confidence: 99%
“…Recently, mutations in TTC19 have been described in young adults with spinocerebellar ataxia [ 2 - 4 ], a 42-year-old man with rapidly progressive neurological disease [ 1 ], and patients with developmental delay in childhood and slowly progressive neurodegenerative disease [ 1 , 5 , 6 ]. So far, 12 cases are documented in the literature.…”
Section: Introductionmentioning
confidence: 99%